Enhanced student attendance and communication in educational management systems - El Mustapha, Louragli; Gmih, Yassine; Soussi, Sohaib; Abdelmajid, Farchi (Bulletin of Electrical Engineering and Informatics, 2025)
The internet of things (IoT) and radio frequency identification (RFID) technology were explored to devise a beneficial approach for managing student attendance. The research developed a system that uses RFID tags embedded in student bracelets to gather presence data via strategically placed sensors. The system leverages real-time databases and Google technologies to enhance the student experience through an online platform, while also utilizing RFID for authentication. Focusing on improving user experience (UX) through effective design, the proposed system offers a pleasurable and cost-effective solution. Developed using popular web technologies such as Firebase, React.js, and Tailwind, along with Arduino chips and sensors, the system provides a practical solution for managing student attendance, academic performance, and administrative communication. The research highlights the potential of RFID technology in improving student management and academic performance. By decreasing the effort needed by traditional systems and proving cost-effective in the long term, it could act as a potential choice for implementation in educational institutions worldwide.